2019
DOI: 10.3389/fnins.2019.01122
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Efficacy, Tolerance, and Hypersensitivity Are Altered After Modulation of SUR1 Subtype KATP Channel Activity in Mice

Abstract: ATP-sensitive potassium (KATP) channels are found in the nervous system and are downstream targets of opioid receptors. KATP channel activity can effect morphine efficacy and may beneficial for relieving chronic pain in the peripheral and central nervous system. Unfortunately, the KATP channels exists as a heterooctomers, and the exact subtypes responsible for the contribution to chronic pain and opioid signaling in either dorsal root ganglia (DRG) or the spinal cord are yet unknown. Chronic opioid exposure (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Injury did not affect ATP sensitivity, inward rectification, unitary conductance or the pharmacological properties of K ATP channels. Although the anti-nociceptive actions of K ATP channel openers has been recognized for many years (Vergoni et al, 1992;Welch and Dunlow, 1993), much of the preclinical work has dealt with the ability of drugs such as pinacidil to potentiate opioid action (Vergoni et al, 1992;Fisher et al, 2019). The relevance of this to therapeutic management of neuropathic pain is yet to be explored.…”
Section: ) Channels In Primary Afferent Neurons and Effect Of Nerve mentioning
confidence: 99%
“…Injury did not affect ATP sensitivity, inward rectification, unitary conductance or the pharmacological properties of K ATP channels. Although the anti-nociceptive actions of K ATP channel openers has been recognized for many years (Vergoni et al, 1992;Welch and Dunlow, 1993), much of the preclinical work has dealt with the ability of drugs such as pinacidil to potentiate opioid action (Vergoni et al, 1992;Fisher et al, 2019). The relevance of this to therapeutic management of neuropathic pain is yet to be explored.…”
Section: ) Channels In Primary Afferent Neurons and Effect Of Nerve mentioning
confidence: 99%
“…The activity of these channels can influence the efficacy of opioids and represent an important factor in tolerance development. Cole Fisher and co-workers demonstrated that the downregulation of SUR1 subtype K ATP channels in the spinal cord and DRG potentiated the development of morphine tolerance and withdrawal syndrome in mice [124]. SUR1 agonists (diazoxide and NN-414) attenuated tolerance development.…”
Section: The Consequence Of Mors Activation On Primary Sensory Neuronsmentioning
confidence: 99%
“…Through influencing the central nervous system, morphine alleviates pain. However, despite the high analgesic potential, it has the potential to be highly addictive if used regularly, in which drug tolerance, physical and psychological dependence are rapidly evolved (4). Long-term use of morphine can change hypothalamus-pituitary-gonads (HPG) axis, which affects the hormones secreted by the anterior pituitary gland, including luteinizing hormone (LH) (5).…”
Section: Introductionmentioning
confidence: 99%